Analysis Of Rewards And Punishments For Improvement Public Sector Employment Ethics Policy In Medan - Arifin, Daud; Ardian, Noni; Triana, Hesti (Universitas Dehasen Bengkulu, 2024)
This study aims to analyze the impact of reward and punishment policies on employee work discipline at the State Civil Service Agency (BKN) Medan. This research uses a quantitative approach with a descriptive correlational survey method. The research population consists of all employees at BKN Medan, with a sample of 150 employees selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple regression analysis. Validity and reliability tests were conducted to ensure that the instruments used were valid and reliable. The results show that reward policies have a significant positive effect on employee work discipline (β = 0.45, p < 0.01), meaning that the better the reward policies implemented, the higher the level of employee work discipline. Punishment policies also have a significant positive effect on employee work discipline (β = 0.35, p < 0.01), indicating that the implementation of firm and fair punishments can improve work discipline. The interaction between reward and punishment policies is not significant (β = 0.10, p > 0.05), suggesting that the combined effect of these policies is not significantly different from the effect of each policy individually. These findings support the motivation and reinforcement theory, which states that positive rewards and negative consequences can influence individual behavior. The practical implications of this research are the importance of designing fair and relevant reward policies and consistently applying punishments to enhance employee work discipline. This study also recommends further research with a qualitative approach and broader scope to deepen the understanding of factors affecting work discipline.